6th ISPAS International Workshop, 22-23 March 2016 - Book of abstracts (Journal of Human Sport & Exercise, 2017)
BOOK OF ABSTRACTS of the 6th ISPAS International Workshop, 22-23 March 2016 in Carlow, Ireland - Contents: 1.Analytics in Sport 2.Performance analysis of football in the blogosphere: Measuring the high press 3.Performance analysis of football in the blogosphere: Goal scoring 4."Don`t forget your roots!" 5.Player rating systems in the invasion-territorial sports: some insights from decision science 6.Efficacy of half-back play in rugby and the impact of substitutions 7.Advanced methods of data analysis and their application to studying performance in team sports 8.Performance indicators that best predict points in professional rugby league 9.A user centred design methodology for the development of technology in performance analysis of sport 10.Predicting the 2015 Rugby Union World Cup 11.Using telecasting to identify turn times in alpine skiing 12.Home advantage within the Six Nations (2000-2015) 13.Risk factors for horse falls in the cross-country phase of national level British Eventing one day events 14.Tennis analysis and tournament design 15.Current physiological parameters of horse riders in equine specific education 16.Horse riding, exercise and fitness programmes: Are horse riders doing enough? 17.Do stride length and height indicate a racehorse`s ability? 18.A ranking system for Gaelic football teams: factors that influence success 19.The statistical analysis of goalkeeper puck-outs during hurling matches 20.Engaging the players in the performance analysis process in a club hurling team 21.A statistical analysis of Kilkenny Senior Hurlers during the 2015 season 22.An analysis of shooting attempts in Inter County Gaelic football 23.Offloading in the 2015 Rugby World Cup 24.European Junior Championships as a pre-requisite for Olympic success in swimming 25.The effect of partial sleep deprivation on agility and vertical jump in basketball players 26.Does the application of pilates into karate training enhance isometric and dynamic core strength of junior karate kumite players?